2015
DOI: 10.1017/ice.2015.135
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Laundry and Textiles in the United States: Review and Commentary on Contemporary Infection Prevention Issues

Abstract: Healthcare professionals have questions about the infection prevention effectiveness of contemporary laundry processes for healthcare textiles (HCTs). Current industrial laundry processes achieve microbial reductions via physical, chemical, and thermal actions, all of which result in producing hygienically clean HCTs. European researchers have demonstrated that oxidative laundry additives have sufficient potency to meet US Environmental Protection Agency benchmarks for sanitizers and disinfectants. Outbreaks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 81 publications
1
30
0
2
Order By: Relevance
“…Despite the fragility of studies in the area, the contamination of aprons, uniforms, and white coats with resistant isolated bacteria from patients hospitalized has been already proven. This reinforces the need for recommendations and actions by the HICC to cease and minimize the pathogenic potential posed by such clothing (14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 65%
“…Despite the fragility of studies in the area, the contamination of aprons, uniforms, and white coats with resistant isolated bacteria from patients hospitalized has been already proven. This reinforces the need for recommendations and actions by the HICC to cease and minimize the pathogenic potential posed by such clothing (14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 65%
“…Based on conventional monitoring methods, government agencies and professional societies have published guidelines suggesting acceptable ranges for operation hospital/clinical building HVAC systems [ 1 ], as well as best practices for handling contaminated textiles and other residuals (i.e., regulated medical wastes) in these unique indoor environments [ 2 ]. While the association of infectious microbes with a wide variety of hospital materials has been indicated by culture-based techniques, the advent and affordability of real-time optical monitoring, together with established molecular techniques, have precipitated new efforts to determine indoor bioaerosol and fomite liberation potential from health care workers’ activities.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies have reported small outbreaks or colonisation of patients associated with contaminated linen or laundering equipment (Sehulster, 2015). Three studies in the published literature implicate contaminated healthcare worker uniforms with HCAI outbreaks (Table 3).…”
Section: Sattar Et Al (2001)mentioning
confidence: 99%